The Effect of Perceived Organizational Support on Job Satisfaction in Nurses through Work-Family Conflict as a Mediator Variable - Ardiani, Dara; Hardjo, Suryani; Turnip, Kaiman (Yayasan Sembilan Pemuda Indonesia, 2025)
This study aims to analyze the influence of perceived organizational support (POS) on nurses’ job satisfaction with work-family conflict (WFC) as a mediator variable. Perceived organizational support (POS) is employees’ perception of the extent to which the organization cares about their well-being. Work-family conflict (WFC) refers to the tension that arises due to an imbalance between work demands and family responsibilities, which can affect job satisfaction. This study uses a quantitative approach with a path analysis method to test the relationship between variables. The results of the analysis showed that POS had a significant effect on WFC with a t-statistical value of 22.033 (>1.96) and a p-value of 0.000 (<0.05), so the first hypothesis was accepted. Furthermore, WFC was shown to have an effect on job satisfaction with a t-statistical value of 10.248 (> 1.96) and a p-value of 0.000 (< 0.05), supporting the second hypothesis. POS also had a direct effect on job satisfaction with a t-statistical value of 3.041 (> 1.96) and a p-value of 0.002 (< 0.05), so that the third hypothesis was accepted. In addition, WFC acts as a mediator in the relationship between POS and job satisfaction, which is shown by a t-statistical value of 3.092 (> 1.96) and a p-value of 0.002 (< 0.05), supporting the fourth hypothesis. The results of this study show that perceived organizational support not only has a direct influence on job satisfaction, but also indirectly through the reduction of work-family conflicts. These findings underscore the importance of creating a supportive work environment to improve nurses’ job satisfaction while reducing conflict between work and family.